Use of organic waste substrates in the production of Senna alata (L.) Roxb. seedlings - Faria, Júlio Cézar Tannure; Caldeira, Marcos Vinicius Winckler; Delarmelina, William Macedo; Rocha, Rafael Luiz Frinhani (Revista Ecologia e Nutrição Florestal - ENFLO, 2014)
The aim of the study was evaluate the growth of seedlings of Senna alata using different combinations and proportions of organic waste, which are: sewage sludge, coffee straw in natura and organic compost (coffee straw in natura and manure) beyond of the commercial substrate. The experiment was conducted in the Nursery for the Center Agricultural Sciences, Federal University of Espírito Santo, on May 6, 2011, and mounted in a completely randomized design (CRD). The seedlings were grown in plastic pots with a capacity of 120 cm³ of substrate remaining 120 days in the shade and another 30 days in the area of rustication. After 150 days of growth were measured the following morphological characteristics: shoot height, stem diameter, ratio between plant height and stem diameter, shoot dry mass, dry mass of root system, total dry mass, dry mass ratio of shoot/root dry mass and Dickson quality index (IQD). It was found that for the production of Senna alata is recommended the use of 60 % sewage sludge with 40% organic compost or 20% sewage sludge with 80 % organic compost, these being the ones that achieved the best average morphological characteristics plant height, stem diameter, shoot dry mass, root dry mass.